Designing an operations research course under active learning strategies (2002)
Various activities and resources that are considered useful for an operations research (OR) class in Icesi University are discussed. The OR class is being offered today to business, industrial engineering, computer engineering and telecommunication engineering majors. The Icesi University is convinced that Active Learning is useful for its students' formative process. It is necessary that the Department Heads on each academic area work with their faculty in the development of curricula that formally introduces these concepts to each of the courses.